The Inflammatory Feed-Forward Loop Triggered by the Complement Component C3 as a Potential Target in Endometriosis - Agostinis, Chiara; Zorzet, Sonia; Balduit, Andrea; Zito, Gabriella; Mangogna, Alessandro; Macor, Paolo; Romano, Federico; Toffoli, Miriam; Belmonte, Beatrice; Morello, Gaia; Martorana, Anna; Borelli, Violetta; et al. (Frontiers in Immunology, 2021)
The complement system is a major component of humoral innate immunity, acting as a first line of defense against microbes via opsonization and lysis of pathogens. However, novel roles of the complement system in inflammatory and immunological processes, including cancer, are emerging. Endometriosis (EM), a benign disease characterized by ectopic endometrial implants, shows certain unique features of cancer, such as the capacity to invade surrounding tissues, and in severe cases, metastatic properties. A defective immune surveillance against autologous tissue deposited in the peritoneal cavity allows a mechanism of immune escape for endometriotic lesions. There is evidence that the glandular epithelial cells found in endometriotic implants produce and secrete the complement component C3. Here, we show, using immunofluorescence and RT-qPCR, the presence of locally synthesized C3 in the ectopic endometriotic tissue, but not in the eutopic tissue. We generated a murine model of EM via injection of minced uterine tissue from a donor mouse into the peritoneum of recipient mice. The wild type mice showed greater amount of cyst formation in the peritoneum compared to C3 knock-out mice. Peritoneal washings from the wild type mice with EM showed more degranulated mast cells compared to knock-out mice, consistent with higher C3a levels in the peritoneal fluid of EM patients. We provide evidence that C3a participates in an auto-amplifying loop leading to mast cell infiltration and activation, which is pathogenic in EM. Thus, C3 can be considered a marker of EM and its local synthesis can promote the engraftment of the endometriotic cysts.